A fatty acid-ordered plasma membrane environment is critical for Ebola virus matrix protein assembly and budding - Souad Amiar; Kristen A. Johnson; Monica L. Husby; Andrea Marzi; Robert V. Stahelin (Journal of Lipid Research, 2024)
Plasma membrane (PM) domains and order phases have been shown to play a key role in the assembly, release, and entry of several lipid-enveloped viruses. In the present study, we provide a mechanistic understanding of the Ebola virus (EBOV) matrix protein VP40 interaction with PM lipids and their effect on VP40 oligomerization, a crucial step for viral assembly and budding. VP40 matrix formation is sufficient to induce changes in the PM fluidity. We demonstrate that the distance between the lipid headgroups, the fatty acid tail saturation, and the PM order are important factors for the stability of VP40 binding and oligomerization at the PM. The use of FDA-approved drugs to fluidize the PM destabilizes the viral matrix assembly leading to a reduction in budding efficiency. Overall, these findings support an EBOV assembly mechanism that reaches beyond lipid headgroup specificity by using ordered PM lipid regions independent of cholesterol.